New insights into phosphorescence properties of LuAGG: Long afterglow phosphor-in-glass for optical data storage. Issue 3 (1st February 2021) - An, J.M.; Zhao, X.; Li, D.S.; Zhang, Y.J.; Fei, F.; Pun, E.Y.B.; Lin, H.
Abstract: Newly long afterglow phosphor-in-glass (PiG) plays pivotal roles in the region of optical data storage. By using solid-phase reactions and unique spectrum modulation methods, a color-tunable PiG with decent persistent phosphorescence which can be tuned from green to blue has been fabricated. Lu3 Al2 Ga3 O12 : Ce 3+, Cr 3+ (LuAGG: Ce 3+, Cr 3+ ) based on TBZNA glass could emit bright green light signal located at 350 and 420 nm ascribed to the 5d1 /5d2 -4f transitions when corresponding optical data was being loadout. The doping of Cr 3+ increases the density of the trap and provides additional traps between the shallow trap and the deep trap to capture more electrons, further improving afterglow decay time. And the storage time and cyclic reading times are derived by the method of thermal stimulation. Thereinto, tunable emission color has been obtained via changing the concentration of Ga 3+, using UV excitation. Moreover, the influence of the Cr 3+ /Ga 3+ on luminescence properties of long-afterglow-PiG materials have been described in detail. Achieved results confirm that it makes LuAGG-PiG as a long afterglow PiG matrix, demonstrating its promising application in optical data storage.